Microstructure of Coal Gangue and Precipitation of Heavy Metal Elements - Huang, Yanli; Li, Junmeng; Song, Tianqi; Sun, Qiang; Kong, Guoqiang; Wang, Fengwan (Journal of Spectroscopy, 2017)
The microstructure and mineral composition of the gangue play a decisive role in the precipitation of heavy metal elements. In this study, the microstructure, mineral composition, and precipitation of heavy metal elements of coal gangue with different weathering degrees were analyzed through electron microscopy, X-ray diffraction, and static immersion leaching experiments. The following results were derived. (1) After the weathering of the coal gangue, its compactness and integrity changed significantly. The coal gangue structure transformed from relatively dense to relatively loose, and the development of large pores and fractures changed from basically no development to significant development. (2) After weathering, the contents of kaolinite and illite significantly increased, while that of feldspar significantly decreased. Coal gangue contains a small amount of Mn, Cu, Zn, Ti, Ba, Cl, and other elements. After weathering, the contents of each element were reduced. (3) Under the same conditions, a higher number of heavy metal elements precipitated from the weathered coal gangue than from the fresh coal gangue. The results of this research have significant importance in revealing the precipitation mechanism of heavy metals from coal gangue and in perfecting the theory of underground water environmental protection during solid backfilling mining.